SURVEI TINGKAT KONDISI FISIK ANGGOTA PANJAT TEBING MAPALA PELITA TAHUN 2022 - Kusnul Sholikhah; Mokhammad Firdaus; Slamet Junaedi (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
The problems of this researcher are: From the discovery of problems, not all of them are used as problems in this study, therefore from the problem "Survey of the Physical Condition Level of Mapala Pelita Rock Climbing Members in 2022. Quantitative descriptive research: population is also not just the number of objects/ the subject or object. So the population in this study were 15 rock climbing members, so the researchers took a total sampling technique to collect a sample of 15 Mapala Pelita rock climbing members. The components of the physical condition include: grip strength test (grib strength), arm muscle strength (pull up), endurance (beep test), speed (run 30 meters), explosive power (standing board jump). Based on the conclusions and results of the research, it can be concluded that research regarding the Level Survey of Physical Conditions of Mapala Pelita members in 2022, the results are in the very good category, there are 1 member (7%), 2 members good (13%), while 1 member (13%) , lacking 4 members (27%) and lacking 6 members (40%). So that in the overall test category of physical conditions it can be concluded that Mapala Pelita 2022 rock climbing members are in the very less category.